Evaluating safety risks of whole-body cryotherapy/cryostimulation (WBC): a scoping review from an international consortium - Legrand, Fabien D.; Dugué, Benoît; Costello, Joe; Bleakley, Chris; Miller, Elzbieta; Broatch, James R.; Polidori, Guillaume; Lubkowska, Anna; Louis, Julien; Lombardi, Giovanni; Bieuzen, François; Capodaglio, Paolo (European Journal of Medical Research, 2023)
Over the two last decades, whole-body cryotherapy/cryostimulation (WBC) has emerged as an exciting non-pharmacological treatment influencing inflammatory events at a cellular and physiological level, which can result in improved sleep quality, faster neuromuscular recovery after high-intensity exercise, and chronic pain relief for patients suffering different types of diseases (fibromyalgia, rheumatism, arthritis). Some evidence even suggests that WBC has benefits on mental health (depression, anxiety disorders) and cognitive functions in both adults and older adults, due to increased circulating BDNF levels. Recently, some safety concerns have been expressed by influential public health authorities (e.g., FDA, INSERM) based on reports from patients who developed adverse events upon or following WBC treatment. However, part of the data used to support these claims involved individuals whose entire body (except head) was exposed to extreme cold vaporized liquid nitrogen while standing in a narrow bathtub. Such a procedure is known as partial-body cryotherapy (PBC), and is often erroneously mistaken to be whole-body cryotherapy. Although having similarities in terms of naming and pursued aims, these two approaches are fundamentally different. The present article reviews the available literature on the main safety concerns associated with the use of true whole-body cryotherapy. English- and French-language reports of empirical studies including case reports, case series, and randomized controlled trials (RCTs) were identified through searches of PubMed, Scopus, Cochrane, and Web of Science electronic databases. Five case reports and two RCTs were included for a total of 16 documented adverse events (AEs). A critical in-depth evaluation of these AEs (type, severity, context of onset, participant’s medical background, follow-up) is proposed and used to illustrate that WBC-related safety risks are within acceptable limits and can be proactively prevented by adhering to existing recommendations, contraindications, and commonsense guidelines.
Keywords: Adverse events; International consortium; Scoping review; Whole-Body Cryotherapy/Cryostimulation (WBC)